CoSe2-decorated NbSe2 nanosheets fabricated via cation exchange for Li storage - Zhang, Jianli (2020)
Though 2D transition metal dichalcogenides have attracted a lot of attention in energy-storage applications, the applications of NbSe2 for Li storage are still limited by the unsatisfactory theoretical capacity and uncontrollable synthetic approaches. Herein, a controllable oil-phase synthetic route for preparation of NbSe2 nanoflowers consisted of nanosheets with a thickness of ∼10 nm is presented. Significantly, a part of NbSe2 can be further replaced by orthorhombic CoSe2 nanoparticles via a post cation exchange process, and the predominantly 2D nanosheet-like morphology can be well-maintained, resulting in the formation of CoSe2-decorated NbSe2 (denoted as CDN) nanosheets. More interestingly, the CDN nanosheets exhibit excellent lithium-ion battery performance. For example, it achieves a highly reversible capacity of 280 mAh g-1 at 10 A g-1 and long cyclic stability with specific capacity of 364.7 mAh g-1 at 5 A g-1 after 1500 cycles, which are significantly higher than those of reported pure NbSe2.